Dust [large type] - Cornwell, Patricia Daniels (Cornwell, Patricia Daniels. Scarpetta series., 2013)
A body, oddly draped in an unusual cloth, has just been discovered inside the sheltered gates of MIT, and it<U+2019>s suspected the identity is that of missing computer engineering grad student Gail Shipton, last seen the night before at a trendy Cambridge bar. It appears she<U+2019>s been murdered, mere weeks before the trial in her $100 million lawsuit against her former financial manager, and Massachusetts Chief Medical Examiner Kay Scarpetta doubts it<U+2019>s a coincidence. She also fears the case may have a connection with her computer genius niece, Lucy. In Dust, Scarpetta and her colleagues are up against a force far more sinister than a sexual predator who fits the criminal classification of a “spectacle killer.” The murder of Gail Shipton soon leads deep into the dark world of designer drugs, drone technology, organized crime, and shocking corruption at the highest levels.